Coupled Atmosphere‐Fire Simulations of the Black Saturday Kilmore East Wildfires With the Unified Model. (18th January 2019) - Toivanen, Jussi; Engel, Chermelle B.; Reeder, Michael J.; Lane, Todd P.; Davies, Laura; Webster, Stuart; Wales, Scott
Abstract: A model for the spread of a wildfire is developed within the U.K. Met Office Unified Model (UM) and used to simulate the Kilmore East fire complex (in southeastern Australia) on Black Saturday (7 February 2009). The UM is configured with four nests with horizontal grid spacings of 4 km, 1.5 km, 444 m, and 144 m. In the first simulation, the UM simply provides predictions of the near‐surface conditions for the wildfire model with no feedbacks to the atmosphere from the fire. In the second, the atmosphere and fire are coupled, allowing the fire to affect the local‐scale weather. The agreement between the coupled simulation and the observed fire behavior is reasonably good. For example, the area burnt is approximately 80% of the actual area burnt. However, such agreement is achieved only by coupling the fire to the atmosphere and, importantly, by igniting 18 additional fires at the times and places the long‐range transport of burning material (spotting) was observed. Without coupling the burnt area is about half of that observed. The calculations reported here suggest that the behavior and spread of fires like the Kilmore East fire are predictable but only when long‐range spotting is included and the atmosphere and fires are coupled. Additional numerical experiments with coarser grids suggest that, although the details of the fire spread are lost, a grid spacing of 1.5 km may be sufficient to simulate the main features of the fire spread. Key Points: A wildfire spread model is coupled to the U.K. Met Office Unified Model and used to simulate the Kilmore East fire There is reasonable agreement between the simulation and the actual Kilmore East fire Such agreement relies on the atmosphere and the fire being coupled and accurate but unforecastable, long‐range spotting